Is reciprocity an enlightening concept to address contemporary issues? - Terradas Saborit, Ignasi (ENDOXA, 2002)
If we want to use reciprocity as an enlightening concept to address contemporary issues, we have to deal with three problems: 1) The lack of consensus among anthropologists for an unique definition. 2) The great differences between an idea or practice of reciprocity primarily related to economics and those provided by relattonships with other fields of social Ufe. 3) The difficulty in dealing with reciprocity after the strong reinterpretations made by the ideology and practice of contrac in different societies.